Pressure, Flow, and Glottal Area Waveform Profile Changes During Phonation Using the Acapella Choice Device - Andrade, Pedro Amarante; Frič, Marek; Saccente-Kennedy, Brian; Hruška, Viktor (Journal of voice : official journal of the Voice Foundation, 2024)
INTRODUCTION: Vibratory positive expiratory pressure (PEP) devices are now commonly used as a resource for voice therapy. PEP devices promote improved vocal economy with the added benefit of producing a massage effect in the vocal tract. Although the benefits of PEP devices for voice have already been demonstrated, their impact on the vocal source is still not very clear. This study assesses the impact of phonation into the Acapella Choice (a type of PEP device) on the voice. METHODS: Three normophonic subjects underwent high-speed videoendoscopy assessment while pressure, flow and electroglottographic data was collected. RESULTS: Phonation into the Acapella device produces large changes in the pressure and flow profiles consequently affecting the voice source. In specific, when intraoral pressure increases as a consequence of the downward movement of the rocker arm in the Acapella device (reduction of the airflow outlet), phonation is hindered, demonstrated by the lower amplitude of vibration of the vocal folds and weaker modulation of the pressure and flow values by the glottal cycle. When the rocker arm in the Acapella device opens (increasing the airflow outlet), the opposite trend is observed where vocal fold vibration is aided and the modulation of pressure and flow by the vocal cycle increases. Based on the pressure and flow signals, we can assume that the impedance of the vocal tract alternates between two dominant regimes: increased inertive reactance (aided vibration) and increased resistance (hindered vibration). CONCLUSIONS: PEP devices, such as the Acapella device, are efficient in modulating the pressure and flow profiles in the vocal tract leading to the alternation of glottal vibration from aided to hindered. These changes in the glottal vibration can be considered an additional consequence of the massage effect caused by the Acapella device.
Keywords: Equipment Design; dospělí; hlasové řasy; hlasový trénink; ventilace umělá s výdechovým přetlakem; Female; Glottis; glottis; elektrodiagnostika; Voice Training; Adult; vibrace; ženské pohlaví; Time Factors; časové faktory; lidé; tlak; laryngoskopie; Vocal Cords; Vibration; Video Recording; Electrodiagnosis; biomechanika; Male; Phonation; Positive-Pressure Respiration; fonace; audiovizuální záznam; mužské pohlaví; Voice Quality; Biomechanical Phenomena; design vybavení; kvalita hlasu; Laryngoscopy; Pressure; Humans